HOW EFL STUDENTS COPE WITH ILL-FORMED SOURCE-LANGUAGE SENTENCES IN ENGLISH-TO-INDONESIAN SIGHT INTERPRETING - Budiarti, Dian; Saehu, Andang (English Review: Journal of English Education, 2023)
This research investigates how English as a Foreign Language (EFL) students cope with ill-formed source-language sentences in English-to-Indonesian sight interpreting. In line with the objective, students’ interpretations of sentences with linguistic errors were collected as the data via video-based observation and qualitatively analyzed using content analysis. The findings reveal that most students were aware of the occurrence of typographical errors in the assigned source documents and able to sight interpret those parts as targeted, especially when dealing with mix-up letters and middle-letter omission. However, many of them seemed to have difficulties in identifying the occurrence of grammatical errors, such as subject-verb disagreement and improper use of a certain part of speech and punctuation errors, such as the presence of unnecessary punctuations, which then leading to inaccurate interpretations. It is assumed that the primary cause of these interpretation problems is attributed to students’ limited understanding of the source texts, highlighting the critical need for enhanced fast-reading comprehension skills among students.